2016
DOI: 10.1155/2016/6135319
|View full text |Cite
|
Sign up to set email alerts
|

Grape Powder Improves Age‐Related Decline in Mitochondrial and Kidney Functions in Fischer 344 Rats

Abstract: We examined the effects and mechanism of grape powder- (GP-) mediated improvement, if any, on aging kidney function. Adult (3-month) and aged (21-month) Fischer 344 rats were treated without (controls) and with GP (1.5% in drinking water) and kidney parameters were measured. Control aged rats showed higher levels of proteinuria and urinary kidney injury molecule-1 (KIM-1), which decreased with GP treatment in these rats. Renal protein carbonyls (protein oxidation) and gp91phox-NADPH oxidase levels were high in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…In mitochondria isolated from kidneys of 23 to 27-month old mice, protein synthesis was two times slower than in mitochondria of young mice [145]. This data correlates with the results of another study, where lower expression of TFAM, a mtDNA transcriptional factor, was detected in the kidneys of 21-month old and young Fischer 344 rats [146]. That study demonstrated a decrease in cytoplasmic and nuclear levels of transcriptional factor Nrf2, which plays an important role in the expression of several antioxidant genes.…”
Section: How Do Mitochondria Change During Aging?supporting
confidence: 89%
See 1 more Smart Citation
“…In mitochondria isolated from kidneys of 23 to 27-month old mice, protein synthesis was two times slower than in mitochondria of young mice [145]. This data correlates with the results of another study, where lower expression of TFAM, a mtDNA transcriptional factor, was detected in the kidneys of 21-month old and young Fischer 344 rats [146]. That study demonstrated a decrease in cytoplasmic and nuclear levels of transcriptional factor Nrf2, which plays an important role in the expression of several antioxidant genes.…”
Section: How Do Mitochondria Change During Aging?supporting
confidence: 89%
“…Particularly, a decline in the activity of mitochondrial enzymes, including those of the Krebs cycle [147] and of the respiratory chain has been demonstrated [148]. Aging was associated with lower respiration rates [146,149], a greater fraction of mitochondria with low potential [18] and a lower rate of ATP production [146].…”
Section: How Do Mitochondria Change During Aging?mentioning
confidence: 99%
“…The mtDNA mutations result from a violation of mtDNA replication and repair (Krishnan et al, 2008), as well as mitophagic dysfunction (Fivenson et al, 2017). In aging organisms, the ability of the Nrf2/ARE cascade to regulate mitochondrial biogenesis is diminished, as it has been demonstrated in rat kidneys (Pokkunuri et al, 2016) and mouse brain (Gureev et al, 2016). On the other hand, various tested chemical compounds displayed their pharmacological effects only in old rodents, which might indicate that the system of adaptive responses in young animals does not require additional external stimuli.…”
Section: Role Of Nrf2 and Pgc-1α In Agingmentioning
confidence: 99%
“…On the other hand, various tested chemical compounds displayed their pharmacological effects only in old rodents, which might indicate that the system of adaptive responses in young animals does not require additional external stimuli. It was found that the geroprotective effects of EPO (Wu et al, 2017), Methylene blue (Gureev et al, 2016), grape powder (Pokkunuri et al, 2016), and β-guanidinopropionic acid (Gureev et al, 2018) can be related to the Nrf2 cascade activation. Several studies demonstrated a decrease in the functional activity of Nrf2 in various organs during aging (Suh et al, 2004; Shih and Yen, 2007; Duan et al, 2009; Ungvari et al, 2011).…”
Section: Role Of Nrf2 and Pgc-1α In Agingmentioning
confidence: 99%
“…For example, epicatechin, quercetin or resveratrol has been shown to lower the oxidative stress in the kidneys and reduce renal damage in animals with cisplatin nephropathy [ 17 , 18 , 19 ], and feeding with anthocyanin-rich food reduces diabetes-associated kidney failure in db/db mice [ 20 ]. A recent study shows that daily drinking of whole grape powder (WGP) prevents age-related decline of kidney function in rats [ 21 ], but its beneficial effect on MetS-associated CKD, a common public health problem in our community [ 22 ], has not been investigated. Obese ZSF1 male rats are generated by a cross between a Zucker diabetic fatty (ZDF) female and a spontaneously hypertensive heart failure (SHHF) male rat, which have MetS similar to humans, including hypertension, type 2 diabetes, hyperlipidemia and nephropathy [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%